Changes in structure and function of diaphragm neuromuscular junctions from BACHD mouse model for Huntington's disease. (February 2016) - de Aragão, Bárbara Campos; Rodrigues, Hermann Alecsandro; Valadão, Priscila Aparecida Costa; Camargo, Wallace; Naves, Lígia Araujo; Ribeiro, Fabíola Mara; Guatimosim, Cristina
Abstract: Huntington's disease (HD) is a neurodegenerative disorder characterized by a progressive decline of motor and cognitive functions. It is caused by a polyglutamine expansion in the huntingtin (htt) protein, which then leads to neurodegeneration that span both the central and peripheral nervous system. Previous works have shown that htt interacts with several proteins from the neurotransmitter release machinery causing synaptic dysfunction. In this work, we looked for alterations in diaphragm neuromuscular junctions (NMJs) from 3 to 4 months old BACHD mouse model for HD. This model represents a new and robust in vivo paradigm for studying the pathogenesis of HD. For optical analysis, NMJs were stained with FM1-43fx and α-bungarotoxin to visualize both pre and postsynaptic elements, respectively. Confocal microscopy optical analysis showed a decrease in the number of synaptic elements and fluorescence intensity in NMJs from BACHD diaphragms compared to WT. We next analyzed presynaptic activity and we observed that synaptic vesicle exocytosis was impaired in NMJs from BACHD diaphragms. Ultrastructural analysis revealed significant changes in the form and sizes of the synaptic vesicles in BACHD diaphragm NMJs that could contribute to impaired exocytosis. Additionally, electrophysiology recordings revealed a decrease in the amplitude of miniature endplate potentials (MEPPs) from BACHD diaphragm NMJs. Our data suggest a dysfunction in BACHD diaphragm NMJs that might occur in other muscles and may aggravate the motor defects seen in HD. These results may contribute to a better understanding of peripheral cholinergic dysfunction in this neurodegenerative disease. Highlights: Pre and post-synaptic elements of BACH neuromuscular junctions are altered. BACHD motor nerve terminals present impairment in synaptic vesicles exocytosis. Synaptic vesicles from BACHD nerve terminals present changes in the size. Neuromuscular junctions from BACHD mice present a decrease in MEPPs amplitude. Motor nerve terminals of BACHD mice are dysfunctional.